Which expression is equivalent to ( xy -6)2 for all values of x and y where the expression is defined?
2 answers:
Answer:
xy^36
Step-by-step explanation:
Answer:
( x y -6)² = x² y² - 12 xy + 36
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given that the expression ( x y -6)²
Apply formula (a-b)² = a² -2ab + b²
( x y -6)² = (xy)² - 2 × xy× 6 + (6)²
= x² y² - 12 xy + 36
( x y -6)² = x² y² - 12 xy + 36
You might be interested in
Answer:
B
Step-by-step explanation:
1 camera = 259
2 cameras = 259 * 2 = 518
So the total price is $518
I live in Florida as well. FL babyeeee. Melly’s hometown yk yk
Answer:
x = 28
Step-by-step explanation:
(3x + 6^o) = 90^o
3x = 84^o
x = 28
19 times 3 equals = 57ft squared. Area = 57ft squared